¿Estilos o modelos? Las planificaciones nacionales para el desarrollo de Chile, Costa Rica y Uruguay a inicios del siglo XXI - Martín Fittipaldi-Freire (Revista Iberoamericana de Estudios de Desarrollo)
In Latin America, different development styles have been tested which have been the result of the location between the real possibilities (linked to the objective conditions defined by their context) and the ideal desires of «being», influenced by the hegemonic trends of thought. The work focuses on analyzing and characterizing the national planning for development of the selected cases (Chile, 2014-2018; Costa Rica, 2015-2018, y Uruguay, 2015-2019), considering the different theoretical currents of development. In this way, it is attempted to generate empirical evidence to describe the development styles that have been tried to adopt in each of the selected countries and, with that, contribute to a general reflection on the main distinctive features of the development experiences that in Latin America They are being assumed at the beginning of this 21st century.